The rredictive value of R wave peak time to detect thrombus burden in st-segment elevation myocardial infarction: a retrospective cohort study in a tertiary medical center - Zehra Güven-Çetin; Bekir Demirtaş; Ahmet Balun; Hülya Çiçekçioğlu; Kerem Özbek (Permanyer, 2023)
Background: Patients with higher thrombus burden have higher procedural complications and more long-term adverse cardiac events. Detecting patients with high thrombus burden (HTB) before coronary intervention could help avoid procedural complications. Objective: The research aimed to analyze the R wave peak time (RWPT) on the electrocardiogram to predict thrombus burden before coronary angiography in patients with acute ST-segment elevation myocardial infarction (STEMI). Materials and Methods: A total of 159 patients with STEMI were included in the study conducted at a tertiary medical center. The thrombolysis in myocardial infarction (TIMI) thrombus scale was applied to assess the thrombus burden. TIMI thrombus grades 0, 1, 2, and 3 were accepted as low; 4 and 5 had HTB. RWPT was measured from the beginning of the QRS complex to the R-peak from the leads pointing to the infarct-related artery. Results: Patients were divided into two groups according to their angiographically defined thrombus burden as low and high. The low thrombus burden group (LTB) comprised fifty-four patients, whereas the HTB group comprised 105 patients. In the LTB group, RWPT was 47.96 ± 9.17 ms, and in the HTB group was 53.58 ± 8.92 ms; it was significantly longer (p < 0.01). Receiver operating characteristic analysis showed that a cut-off value of preprocedural RWPT of > 46.5 ms predicted the occurrence of HTB with a sensitivity and specificity of 87.62% and 51.85%, respectively (AUC 0.682, 95% CI 0.590-0.774, p < 0.001). Conclusion: The present study evaluated the relationship between the RWPT and thrombus burden in STEMI patients. Based on the results, RWPT is an independent predictor of HTB.